High-Energy Charged Particles for Spatially Fractionated Radiation Therapy - Guardiola, Consuelo; Prezado, Yolanda (Frontiers in Physics, 2020)
Spatially fractionated radiotherapy (SFRT) offers a gain in normal tissue sparing with respect to standard seamless irradiations. The beneﬁts of SFRT may be further enhanced by replacing the commonly used photon beams by charged particles. Along this line, proton SFRT has already shown a signiﬁcant widening of the therapeutic window for radioresistant tumors in preclinical studies.The goal of this work was to investigate whether the use of superior energies as compared to the clinical ones, as well as heavy ions could lead to a further improvement of SFRT. New facilities like FAIR, RAON or some others associated to the International Biophysics collaboration will be able to provide very intense high energy ion beams, enabling the experimental evaluation of the Monte Carlo simulations reported in this work. Our results indicate that proton SFRT could beneﬁt from the use of higher beam energies (˜1GeV). Concerning heavy ions, such as carbon or neon, the main advantage would be the possible theragnostic use. Biological experiments are needed to validate these results and they will be the subject of future experimental proposals at those new facilites.